The Symbolic Interaction between the Worship Leader and the Music Ministers in Christian Accompaniment Music at Isa Almasih Church, Deliksari Gunungpati, Semarang - Ciptoningtyas, Sheila Vallenta; Susetyo, Bagus (Universitas Negeri Semarang, 2024)
Music is an important component of Christian worship in churches, which serves as the accompanying music. This is particularly true in charismatic churches, which primarily use contemporary music that evolves with current trends. In charismatic Christian worship, music plays a role in accompanying and creating the atmosphere for praise and worship songs. This research addresses the issue of symbolic interaction between worship leader and the accompanying music in Christian worship at Isa Almasih Church, Deliksari Gunungpati Semarang. This research employed descriptive qualitative method and used data collection techniques, namely observation, interviews, and documentation. Triangulation was used to ensure the data validity. For analysis, this research used data reduction, data presentation, drawing conclusions, and verification. The findings show that the symbolic interactions between the worship leader and music ministers during worship involves music elements such as pitch, dynamics, rhythm, tempo, melody, and tone color or timbre. This symbolic interaction is formed through agreements made during practice sessions between the worship leader and the music ministers.